Architectural sculpture in the Byzantine Negev characterization and meaning - Golan, Karni, 1979- (Archaeology of the Biblical worlds ;, 2020)
This book presents a study and catalogue of the early Christian stone architectural decorations from the Negev Desert (Israel). This work is based on the largest sample of decorated architectural elements from the Byzantine Negev (4th-7th century CE) to have been comparatively studied. The analysis provides a key for the characteristics of these aniconic, carved decorations, and an in-depth examination of their symbolic meaning.